1991
DOI: 10.1038/jcbfm.1991.133
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Binding of Nimodipine in the Brain: I. The Effect of Focal Cerebral Ischemia

Abstract: Summary:We report the regional variation in [3H]nimodipine binding in vivo during focal cerebral isch emia. After intravenous injection, 30 min of circulation of eH]nimodipine was sufficient to establish a secular equi librium of distribution in the brain. Rats sustained left middle cerebral and common carotid artery occlusions for 5 min, and 4, 24, and 48 h (n ?o 6 per group). They were decapitated 30 min after injection of 250 /l-Ci of eH]nimodipine and their brains were submitted to auto radiography. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…We have reported that in vivo binding to [ 3 H]nimodipine may rapidly indicate those ischemic brain regions vulnerable to the development of infarction. 13 In the same model of MCA+CCA occlusion, the superior and lateral caudate showed increased volumes of distribution of [ 3 H]nimodipine within 5 minutes after occlusion, but the volume was greater in the overlying cortex 4 hours later. This suggests that such measurements could become reliable early indicators of the ischemic penumbra at a stage when therapeutic intervention is possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported that in vivo binding to [ 3 H]nimodipine may rapidly indicate those ischemic brain regions vulnerable to the development of infarction. 13 In the same model of MCA+CCA occlusion, the superior and lateral caudate showed increased volumes of distribution of [ 3 H]nimodipine within 5 minutes after occlusion, but the volume was greater in the overlying cortex 4 hours later. This suggests that such measurements could become reliable early indicators of the ischemic penumbra at a stage when therapeutic intervention is possible.…”
Section: Discussionmentioning
confidence: 99%
“…recently, the predominant concerns have been the precise MCA segment to be coagulated, 1 the influence of the strain used, 2 and variability in the location and incidence of the resulting infarction. 13 More recently, the temporal profile of regional cerebral blood flow (CBF) and the histopathologic changes occurring after MCA occlusion have received some attention. Bolander and his colleagues 4 showed that CBF was lowest during the hours following vascular occlusion but that many regions showed significant reperfusion.…”
mentioning
confidence: 99%
“…Directly injecting magne sium into the CA 1 following 24 h of reperfusion is also potently cytoprotective by postsynaptic Ca 2 + channel blockade (Tsuda et aI., 1991). It is known that N-type Ca 2 + channels are restricted largely to neurons (Hillyard et aI., 1992) and are approxi mately 24-fold more dense than nimodipine binding sites, which have been implicated both in transient focal ischemia (Hakim and Hogan, 1991) and in transient forebrain ischemia (Takizawa et aI., 1994). While the primary physiological function of N-type Ca2+ channels may be to mediate transmitter re lease, in these pathological situations there may be J Cereb Blood Flow Me/ab, Vol.…”
Section: Discussionmentioning
confidence: 99%
“…By administration of the Ca 2+ entry blocker nimodipine the detrimental accumulation of Ca 2+ was reduced, and electroencephalographic recovery as well as histological changes were improved in comparison with the control group. Moreover, labeled nimodipine can be used as a marker of activated Ca 2+ channels 30 ; in regions with dense ischemia that later were found infarcted, [ 3 H]nimodipine binding increased earlier than in areas of milder hypoperfusion. When binding declined in a region where it was previously increased, infarction was likely to develop.…”
Section: Chemical Markers Of Ischemic Damagementioning
confidence: 99%